Analisis Risiko Keselamatan dan Kesehatan Kerja dengan Metode HIRARC pada Perawat di Instalasi Rawat Inap RSI Ibnu Sina Pekanbaru - Yusmaini, Yusmaini; Rahayu, Endang Purnawati; Alamsyah, Agus (Jurnal Kesehatan Komunitas, 2024)
Nurses in carrying out their duties have the risk of having a work accident or getting an occupational disease. Based on data from RSI Ibnu Sina Pekanbaru it was recorded that work accidents that occurred to nurses included cases of being stabbed by a needle, slipping, officers being squeezed by a stretcher, and slashing. The purpose of this study was to analyze hazard identification, risk assessment, and risk control using the HIRARC Method for Nurses at the Inpatient Installation of RSI Ibnu Sina Pekanbaru with 10 informants. Collecting data using in-depth interviews, observation, and document review and processing using the triangulation method, namely the researcher carried out observations, and looked at archives as well as pictures and photos.  The results showed the identification of dangers, namely needle stick wounds, contracting Hepatitis A, Hepatitis B, HIV/AIDS, wrong posture and anxiety about contracting infectious diseases, high-risk assessment of drug injection, infusion, blood sampling, and control. Risk, namely substitution, administrative, and personal protective equipment. The conclusion of this study states that the identification of hazards in inpatient installations are mechanical hazards, biological hazards, ergonomic hazards, and psychosocial hazards. The highest risk value is mechanical hazards, namely needle sticks resulting in needle stick wounds and contracting infectious diseases. The existing hazard controls are SOP and personal protective equipment. Suggestions need to be increased monitoring of officer compliance, socialization of SPOs, monitoring of incident reporting, ergonomic training, and routine health check programs.